ANALISIS LINGKUNGAN INTERNAL DAN EKSTERNAL DALAM MENETAPKAN STRATEGI UNTUK KEBERLANGSUNGAN HIDUP PERUSAHAAN (Studi Kasus Pada Industri Rumah Tangga Keripik Tempe Ri-Mas Malang) - Rafika Epsilani Cymbidiana; Rosi di (Jurnal Ilmiah Mahasiswa FEB, 2012)
The objective of the research is to show that through the SWOT analysis can be formulated a strategy that appropriate with the company condition  thus strengthening the company's position to survive. This  research was conducted in one of the home industry in Malang city, Keripik Tempe Ri-Mas. Methods of data collection in this study included observations, interviews, and documentation, with the type of research is descriptive. Descriptive research is a type of research that describes the existing situation, without intended to  take  conclusions.  The method of analysis used in this research is qualitative analysis method, with the instrument analysis is  SWOT analysis, including the analysis of internal and external environment. The result of this research indicate that the SWOT analysis is capable to  make  a  formulation strategy  that appropriate with the company condition  and strengthening  the company's position in the competition. SWOT analysis identifiy  strengths, weaknesses, opportunities, and threats by analyzing the internal and external environment. SWOT analysis has an  important role for the development and survival of the company, by helping to develop and implement effective, productive, and efficient  strategies and help to describe  the success key of the company.Keywords :  SWOT analysis,  internal environment analysis, external environment analysis, strategy.